Breaking the Waves: How the Phenomenon of European Jihadism Militates Against the Wave Theory of Terrorism - Proshyn, Denys (International Studies. Interdisciplinary Political and Cultural Journal, 2015)
David Rapoport’s Wave theory of terrorism is one of the most oftencited theories in the literature on terrorist violence. Rapoport is praised for having provided researchers with a universal instrument which allows them to explain the origin and transformation of various historical types of terrorism by applying to them the concept of global waves of terrorist violence driven by universal political impulses. This article, testing the Wave theory against the recent phenomenon of homegrown jihadism in Europe, uncovers this theory’s fundamental weaknesses and questions its real academic and practical value.